2015
DOI: 10.3109/23744235.2015.1062536
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of ESBL disseminating plasmids

Abstract: Bacteria producing extended-spectrum β-lactamases (ESBLs) constitute a globally increasing problem that contributes to treatment complications and elevated death rates. The extremely successful dissemination by ESBL-producing Enterobacteriaceae during the latest decades is a result of the combination of mobilization, evolution and horizontal spread of β-lactamase genes on plasmids. In parallel, spread of these plasmids to particularly well-adapted bacterial clones (outbreak clones) has expanded. In this review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
61
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 68 publications
3
61
0
Order By: Relevance
“…Currently, there are different 172 CTX-M β-lactamases types (http://www.lahey.org/studies/), clustered into five phylogroups (CTX-M-1, -2, -8, -9 and -25). CTX-M-1 phylogroup, which includes CTX-M-15, is the most widely distributed all over the world [8]. …”
mentioning
confidence: 99%
“…Currently, there are different 172 CTX-M β-lactamases types (http://www.lahey.org/studies/), clustered into five phylogroups (CTX-M-1, -2, -8, -9 and -25). CTX-M-1 phylogroup, which includes CTX-M-15, is the most widely distributed all over the world [8]. …”
mentioning
confidence: 99%
“…In selection of donor strains, we focused on ESBL strains, as studies show that ESBL determining gene is usually plasmid borne, [19][20] and successful conjugation could easily be spotted by screening for transference of factors for resistance to Cefotaxime, Ceftazidime, etc. Our study too demonstrated the presence of ESBL genes on plasmids by successful conjugation in 2 out of 7 eligible donor ESBL Escherichia coli isolates ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…With fast and robust diagnostics of resistance, adequate treatment could be administered directly, existing antibiotics could be used more efficiently and “last resort” antibiotics could be spared2. A key reason for the rapid spread of antibiotic resistance is horizontal transfer of resistance genes located on mobile genetic elements, such as plasmids3. Recently, plasmid-mediated resistance to last resort antibiotics, such as carbapenems4 and polymyxins5, have been reported.…”
mentioning
confidence: 99%
“…These methods are now increasingly being replaced by next generation DNA sequencing approaches8, providing basepair resolution. Despite the improvement of sequencing techniques during the last decades, assembling plasmid sequences is not trivial due to their dynamic and repetitive nature which often requires time-consuming downstream bioinformatics analysis to obtain the complete picture3. Furthermore, whole genome sequencing is so far dependent on bacterial cultivation, DNA preparation, sequencing library preparation and long data collection procedures and is therefore slow, hampering its use in rapid diagnostics.…”
mentioning
confidence: 99%
See 1 more Smart Citation